2021
DOI: 10.3390/ijms22158105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Melanogenesis Activity of Enriched Pueraria lobata Stem Extracts and Characterization of Its Phytochemical Components Using HPLC–PDA–ESI–MS/MS

Abstract: The root of Pueraria lobata (Willd.) is a widely used herbal medicine worldwide, whereas the stem of the plant is discarded or used as feed for livestock. To reuse and exploit the stem of P. lobata as a resource, we investigated its potential as a skin-whitening agent. We found that the developed, enriched P. lobata stem (PLS) extract significantly inhibited melanin production in the 3-isobutyl-1-methylxanthine-induced B16/F10 cells at a concentration of 50 μg/mL. To further confirm the mechanism of the antime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…α-MSH is secreted from the middle of the pituitary gland and binds to melanocortin 1 receptor, a membrane receptor expressed only in melanocytes, which activates adenylyl cyclase. This in turn amplifies the intracellular cAMP signal, induces protein kinase A (PKA) activation, and increases the expression of MITF (a transcription factor specific to melanocytes) by activating intracellular cAMP response element binding protein (CREB) [ 54 ]. Melanin is synthesized through intracellular signaling mechanisms, among which cAMP/PKA is the main pathway.…”
Section: Resultsmentioning
confidence: 99%
“…α-MSH is secreted from the middle of the pituitary gland and binds to melanocortin 1 receptor, a membrane receptor expressed only in melanocytes, which activates adenylyl cyclase. This in turn amplifies the intracellular cAMP signal, induces protein kinase A (PKA) activation, and increases the expression of MITF (a transcription factor specific to melanocytes) by activating intracellular cAMP response element binding protein (CREB) [ 54 ]. Melanin is synthesized through intracellular signaling mechanisms, among which cAMP/PKA is the main pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Stock solutions (5 mg/mL) were prepared in dimethyl sulfoxide (DMSO, Sigma, St. Louis, MO, USA) and were then diluted to proper concentrations in the growth medium. Cell viability was evaluated by EZ-Cytox assay kit (Daeil Lab Service Co. Ltd., Seoul, Korea) as described previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure for visual evaluation of melanosis was performed following the method previously recorded [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ultraviolet radiation can directly affect melanocytes, regulate the expression of melanogenic enzymes, and cause skin photoaging [ 12 ]. Some studies have shown that natural plants play an important role in skin whitening by inhibiting tyrosinase expression and alleviating the excessive accumulation of melanin caused by ultraviolet light [ 13 ].…”
Section: Introductionmentioning
confidence: 99%